Respuestas
Respuesta dada por:
0
Respuesta:
amigo esa ecuasion ni goglee sabe
Anónimo:
xd
Respuesta dada por:
1
Respuesta:
Sale que x= -3
Explicación paso a paso:
4 (- 5x - 2 + 2x) = 28
4(−3x−2) = 28
−3x − 2 =2 8/4
−3x −2 = 7
−3x = 7 + 2
−3x = 9
x = -9/3
x = -3
comprobación:
4(−5(-3) − 2 + 2(-3)) = 28
4(15 − 2 + 2(−3)) = 28
4(15− 2−6) = 28
4(13 − 6) = 28
4 * 7 = 28
28 = 28
espero q te ayude :D
Salu2✨
Preguntas similares
hace 4 años
hace 4 años
hace 4 años
hace 7 años
hace 7 años
hace 7 años
hace 8 años